Analysis of Geographical Conditions against Socio-Political and Legal Dynamics in Pre-Islamic Mecca and Medina: A Historical and Critical Approach - Solihan Makruf; Lis Diana Ningsih; Syahrul Anwar (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research is motivated by the fact that geographical conditions played an important role in shaping the social, political and legal dynamics in pre-Islamic Makkah and Madinah. This research aims to analyse how geographical factors influenced the development of social structures, political systems and legal norms in the two cities before the advent of Islam. This research adopts a normative legal approach and a descriptive method of analysis. Data was collected using literature review techniques from historical, legal and social sources related to the pre-Islamic period. The data was then analysed using qualitative data analysis techniques to understand the relationship between geographical conditions and the dynamics that occurred. The results of this study show that the geographical conditions of Makkah and Madinah, such as their strategic location on trade routes and challenging geographical environment, contributed to the formation of a hierarchical social structure and a political system based on clan power. The legal system also evolved according to the pragmatic needs of the local community to maintain social and economic stability. The findings of this study suggest the need for a deeper understanding of the relationship between geography and socio-political dynamics as a basis for studying the transformation of law and community structure, especially in areas that have experienced significant historical change.